Efektivitas Konseling Kelompok Dengan Teknik Assertive Training Dalam Meningkatkan Self Esteem Peserta Didik - Febrianti, Dila; Nikmarijal, Nikmarijal (IJoCE: Indonesian Journal of Counseling and Education, 2024)
Self-esteem is an individual's ability to assess, appreciate, and accept themselves, both in terms of strengths and weaknesses, while recognizing and developing all aspects within themselves. This assessment reflects the attitude of approval or disapproval towards oneself and indicates the extent to which an individual believes they are capable, valuable, successful, and worthy. Low self-esteem can make it difficult for students to evaluate and assess themselves. This issue is observed among some 10th-grade students at SMA Negeri 2 Sungaiselan, where students exhibit low confidence, such as being afraid or shy to express opinions, having difficulty refusing requests, and struggling to say "no." To address this problem, efforts are needed to improve self-esteem through group counseling with assertive training techniques. This study aims to determine the effectiveness of group counseling using assertive training techniques in improving the self-esteem of 10th-grade students at SMA Negeri 2 Sungaiselan. The research used a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. Two groups were involved: an experimental group and a control group, both of which underwent pretests and posttests. Data collection was carried out through observation, documentation, and self-esteem questionnaires. The sampling technique used was purposive sampling, with 16 students divided into two groups: 8 students in the experimental group and 8 students in the control group. The hypothesis testing results using the Independent Sample T-Test in SPSS 25 showed that the significance value (sig 2-tailed) was smaller than 0.005 (0.001 < 0.005), indicating that Ha was accepted and Ho was rejected. Additionally, the gain score of the experimental group was higher than the average gain score of the control group (9.57 > 5.11). This proves that group counseling using assertive training techniques is effective in improving the self-esteem of 10th-grade students at SMA Negeri 2 Sungaiselan.